A laboratory study to test the responses of human dental pulp stem cells to extracts from three dental pulp capping biomaterials. (7th March 2021) - Abou ElReash, A.; Hamama, H.; Grawish, M.; Saeed, M.; Zaen El‐Din, A. M.; Shahin, M. A.; Zhenhuan, W.; Xiaoli, X.
Abstract: Aim: This laboratory study aimed to investigate the effects of three endodontic biomaterials; MTA‐HP, iRoot‐BP‐Plus and ACTIVA on the proliferation, adhesion and osteogenic differentiation of human Dental Pulp Stem Cells (hDPSCs). Methodology: The hDPSCs were isolated from the dental pulps of 21 patients scheduled for surgical extraction of their impacted third molars. The MTT assay was used for assessing cellular proliferation. Ninety‐six‐well plates were used and the experiment was repeated four times under the same condition and the assay was done in triplicate. Four groups were assigned in which the hDPSCs were cultured in complete media only and considered as negative control. Whilst in the 2 nd, 3 rd and 4 th groups, the cells were treated with CM supplemented with 1.5 μl MTA‐HP (CM‐MTA, iRoot‐BP‐Plus (CM‐BP), and ACTIVA(CM‐AC) extracts, respectively. Attachment adhesion and growth morphology of hDPSCs were observed using SEM and the osteogenic differentiation assay was evaluated by Alizarin red stain test (ARS). The data of proliferation and osteogenic differentiation were analysed using two‐way ANOVA followed by Tukey's post hoc multiple comparison test. A p‐value < 0.05 was considered significant to analyse the differences amongst the means of groups. Results: Both CM‐MTA and CM‐BP groups were associated with a significant increase in hDPSC proliferation in comparison with CM‐AC and CM groups (p = 0.001). hDPSCs exhibited a greater cellular attachment to iRoot‐BP‐Plus surfaces followed by MTA‐HP, whilst less attachment was observed in the ACTIVA group. Moreover, at day 7 there was a significant difference in formation of mineralizing nodules; CM‐BP, CM‐MTA and CM‐AC groups respectively (p = 0.001). Whilst there was no significance of difference between CM‐AC and CM groups (p > 0.05). Conclusions: In a laboratory setting, ACTIVA, MTA‐HP and iRoot‐BP‐Plus promoted hDPSCs proliferation, mineralization and attachment, which may explain their in‐situ success as endodontic biomaterials.